Utilisation of monoclonal antibodies in the single radial immunodiffusion assay to determine potency and stability for seasonal and pandemic influenza vaccines - Bodle, Jesse; Burge, David; Gounder, Gopal; Vandenberg, Kirsten; Laurie, Karen; Rockman, Steven (Frontiers in Immunology, 2025)
IntroductionFollowing manufacture, influenza vaccines are required to undergo potency testing as part of the release process to market. The single radial immunodiffusion (SRID) assay is currently the compendial standard for determining the antigen potency and stability of protein-based influenza vaccines. This assay relies on polyclonal antibodies from animal serum to bind protein antigens in a gel, resulting in a visible precipitin ring. The diameter of this ring is then compared to a calibrated standard to quantify potency. However, the production of polyclonal antiserum introduces delays, impacting the timely release of both seasonal and pandemic vaccines. There is a need for alternative methods that can expedite vaccine release without compromising accuracy or reliability.MethodsMonoclonal antibodies (mAbs) specific to influenza haemagglutinin (HA) proteins were generated and characterised. Particular mAbs were identified for their ability to react with a broad range of influenza virus strains across different years and seasons, despite antigenic drift and periodic vaccine updates. These mAbs were prepared in advance of the emergence of dominant virus clades, enabling improved pandemic preparedness. In this study, a blend of two mAbs—each targeting distinct regions of the HA protein (the globular head and the stem)—was utilised in an SRID assay format. The assay’s performance was benchmarked against the traditional polyclonal animal sera-based SRID assay for both potency and stability measurements of seasonal and pandemic influenza vaccines. ResultsThe combination of two mAbs with alternate specificity enabled the successful precipitation of antigen in the SRID assay. The results obtained from the mAb-based SRID assay demonstrated strong correlation with those from the standard polyclonal sera-based assay. Both potency and stability assessments for various influenza virus samples—including seasonal and pandemic strains—showed comparable outcomes between the two assay formats. The use of specific mAbs allowed for consistent reactivity across multiple influenza seasons, regardless of antigenic drift. DiscussionThis study demonstrates that a mAb-based SRID assay is a viable alternative to the conventional polyclonal sera-based approach for influenza vaccine potency and stability testing. The capacity to generate and stockpile mAbs prior to the dominance of specific virus clades offers the potential for rapid assay deployment, thereby reducing the time required for vaccine release, particularly in pandemic scenarios. Importantly, the adoption of mAb-based assays may not necessitate extensive clinical trials, further expediting the process. Overall, by utilising a carefully selected and well-characterised mix of monoclonal antibodies, this strategy has the potential to substantially improve preparedness and response to emerging influenza threats while upholding rigorous quality standards.